INTERNAL AND EXTERNAL FACTORS ON STATE-OWNED ENTERPRISES STOCK PRICES - Roseno, Haris; Sufyati HS; Mahjus Ekananda Sitompul (International Journal of Social Science, 2023)
Stocks are proof of ownership with their value determining the amount of control over a company. Shares are securities aimed at obtaining fresh funds from investors, for investor's stocks are investments that provide ownership rights. Share prices are determined by demand and supply made by investors. However, investors before making transactions on the stock exchange will conduct an analysis involving external and internal factors. The purpose of this study is to determine the effect of external and internal factors on the stocks prices of state-owned enterprises which are majority owned by the state and of course get privileges and full support from the government. This study uses panel data which aims to analyze the influence of external and internal factors on the stock prices of 14 State-Owned Enterprises listed on the Indonesia Stock Exchange from 2015 to 2020. Using the multiple regression analysis method with the fixed effect model as the selected model, the results show that factors Externally, namely Indonesia's trade balance and the exchange rate, it has a significant negative effect, while internal factors, consisting of the current ratio and debt to equity ratio, also have a significant negative effect on SOE stock prices